2011
DOI: 10.1186/cc10536
|View full text |Cite
|
Sign up to set email alerts
|

A handoff is not a telegram: an understanding of the patient is co-constructed

Abstract: Hospital handoffs are believed to be a key locus of communication breakdown that can endanger patient safety and undermine quality of care. Substantial new efforts to better understand handoffs and to improve handoff practices are under way. Many such efforts appear to be seriously hampered, however, by an underlying presumption that the essential function of a handoff is one-way information transmission. Here, we examine social science literature that supports a richer framing of handoff conversations, one th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 38 publications
8
89
0
Order By: Relevance
“…Without handoff education, the nursing students lacked awareness of the importance of an active handoff recipient in creating a shared mental model. Consistently with the current research result [34] describes the necessity of both provider and receiver actively participating in the co-construction of the oncoming caregiver's understanding of the patient in order to promote patient safety. In the same issue [30] found that the nursing handoff educational training program improved handoff communication skills in nursing students.…”
Section: Discussionsupporting
confidence: 69%
“…Without handoff education, the nursing students lacked awareness of the importance of an active handoff recipient in creating a shared mental model. Consistently with the current research result [34] describes the necessity of both provider and receiver actively participating in the co-construction of the oncoming caregiver's understanding of the patient in order to promote patient safety. In the same issue [30] found that the nursing handoff educational training program improved handoff communication skills in nursing students.…”
Section: Discussionsupporting
confidence: 69%
“…Transfer of a patient transfer requires procedural routines, waiting times, and paperwork, which are often specific to the partner organization (Hilligoss and Cohen, 2011). Patient referral/receipt to/from many partners with diverse working procedures substantially increases the operational burden related to patient referrals and the risks of diagnostic mistakes, imperfect treatment, and suboptimal referral decisions (Cohen et al, 2012). Limited variety of referral partners' capabilities, poorly specialized coordination dynamics, and lack of fruitful learning opportunities associated with dense relationships may negatively affect the effectiveness of care delivered to patients.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Veinot et al (2012) documented wide reliance on a collective, repeated, and stable set of activities established by partner hospitals for patient sharing in the context of the US Medicare system. These interorganizational routines provide important learning opportunities, especially regarding patient care and appropriate ways of addressing clinical problems (Hilligoss and Cohen, 2011;Cohen et al, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A handoff encompasses the exchange of information between clinicians to facilitate continuity of care. When handoffs are used to facilitate continuity for a limited period of time, as when clinicians take over care for only the nighttime, the nighttime clinician is providing cross-coverage (1). The number of handoffs has increased considerably because of changes in work hour regulations for residents (2), which makes these handoffs an important target for quality improvement interventions.…”
mentioning
confidence: 99%